2005
DOI: 10.2135/cropsci2003.0664
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Maize from Pollen‐Mediated Gene Flow by Time and Distance

Abstract: grains, a number greatly in excess of that needed for fertilization (Uribelarrea et al., 2002). However, the pol-Development of improved genetic traits in maize (Zea mays L.) relen of maize is among the largest and heaviest of the quires robust measures to prevent pollen-mediated gene flow (PMGF) grasses, with a diameter of about 90 m. For compariand assure isolation of new traits, whether these traits are the result son, the pollen grains of ragweed (Ambrosia spp.) and of conventional breeding or of modern ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 25 publications
7
73
0
6
Order By: Relevance
“…Similar reductions in hybridization rates have been reported for corn, a wind pollinating species (Della Porta et al, 2008;Halsey et al, 2005;Messeguer et al, 2006;Palaudelmas et al, 2008;Rognli et al, 2000). These studies also evaluated the relationship between flowering overlap, distance, and hybridization frequency, and showed that increasing temporal isolation reduced the spatial distance required to achieve lower levels of cross pollination.…”
Section: Effects Of Temporal and Spatial Factorssupporting
confidence: 75%
“…Similar reductions in hybridization rates have been reported for corn, a wind pollinating species (Della Porta et al, 2008;Halsey et al, 2005;Messeguer et al, 2006;Palaudelmas et al, 2008;Rognli et al, 2000). These studies also evaluated the relationship between flowering overlap, distance, and hybridization frequency, and showed that increasing temporal isolation reduced the spatial distance required to achieve lower levels of cross pollination.…”
Section: Effects Of Temporal and Spatial Factorssupporting
confidence: 75%
“…However, defining the appropriate isolation perimeter width is complicated: various biological, physical, experimental and analytical factors with varying levels of importance play a role in the study of cross-fertilisation in maize (Devos et al, 2005). To take the factors that are relevant for co-existence into account, recent empirical crossfertilisation studies mimic worst-case commercial on-farm situations (Halsey et al, 2005;Della Porta et al, 2006;Goggi et al, 2006;Pla et al, 2006;Weber et al, 2007;Weekes et al, 2007). In Spain, out-crossing studies are even performed in real agricultural situations of co-existence.…”
Section: Eu Countries Eventsmentioning
confidence: 99%
“…Plots were planted under biosafety conditions, isolated by at least 500 m from commercial corn plantings, and planted at least 21 d later than recommended; delayed planting avoids cross-pollination with non-GM corn in accordance with government regulations for field tests with GM corn (Halsey et al 2005;LBOGM 2005). Bt corn hybrids used in these tests were Agrisure TM 3000 GT with Cry1Ab and mCry3A proteins that provide resistance to Lepidoptera and Coleoptera, respectively; Agrisure® Viptera TM 3110 with Cry1Ab and Vip3A20 providing resistance to Lepidoptera, and Agrisure® Viptera TM 3111 with proteins Cry1Ab and Vip3Aa20 providing resistance to Lepidoptera and mCry3A to Coleoptera.…”
Section: Methodsmentioning
confidence: 99%